Artificial Intelligence Awareness and Readiness among Undergraduate Students in Islamic Higher Education - S, Kartika (LinguaEducare: Journal of English and Linguistic Studies, 2025)
This study investigates the levels of awareness and readiness toward Artificial Intelligence (AI) among undergraduate students in Islamic higher education, focusing on English Language Education students at UIN Raden Intan Lampung. Using a quantitative survey design, data were collected from 150 students through a structured questionnaire that measured four dimensions of AI literacy: awareness, usage, evaluation, and ethics. Descriptive and inferential statistics were employed to analyze the findings. The results indicate that students demonstrated relatively high awareness of AI applications, particularly in recognizing its potential for academic support. However, their ability to evaluate AI-generated outputs was limited, with many reporting low confidence in judging accuracy and bias. Usage was moderate, showing frequent reliance on AI tools for grammar correction and information retrieval but without strategic application. Ethical awareness was also moderate, with students expressing concern about plagiarism but less knowledge of issues such as algorithmic fairness and data privacy. Differences were found across year levels and prior AI experience, with senior students and those with exposure outside the classroom displaying higher readiness. The study highlights the urgent need for targeted curriculum reform, faculty training, and institutional policies that integrate AI literacy within an ethical and culturally grounded framework.